2018
DOI: 10.1007/s12035-018-0900-8
|View full text |Cite
|
Sign up to set email alerts
|

Herp Promotes Degradation of Mutant Huntingtin: Involvement of the Proteasome and Molecular Chaperones

Abstract: In neurodegenerative diseases, pathogenic proteins tend to misfold and form aggregates that are difficult to remove and able to induce excessive endoplasmic reticulum (ER) stress, leading to neuronal injury and apoptosis. Homocysteine-induced endoplasmic reticulum protein (Herp), an E3 ubiquitin ligase, is an important early marker of ER stress and is involved in the ubiquitination and degradation of many neurodegenerative proteins. However, in Huntington's disease (HD), a typical polyglutamine disease, whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…However, the upregulation of Herp expression can reduce the level of mHTT but is unable to clear it out entirely. Thus, the authors speculate that upregulated Herp can only delay the progression of HD and not prevent it [122].…”
Section: Disrupted Proteolytic Pathways: Ptms In Abnormal Htt Proteinmentioning
confidence: 98%
“…However, the upregulation of Herp expression can reduce the level of mHTT but is unable to clear it out entirely. Thus, the authors speculate that upregulated Herp can only delay the progression of HD and not prevent it [122].…”
Section: Disrupted Proteolytic Pathways: Ptms In Abnormal Htt Proteinmentioning
confidence: 98%
“…In fact, an important interference was attributed to sequestration and depletion of p97/VCP and its cofactors Npl4 and Ufd1 by mHtt, which would not cause global UPS deficiency, but rather a crippling dysfunction of ERAD (Duennwald and Lindquist, 2008; Yang et al, 2010; Leitman et al, 2013). Homocysteine-induced endoplasmic reticulum protein (Herp), an important factor in ERAD, was recently reported to be directly involved in targeting of mHtt for degradation (Luo et al, 2018). The inhibition of ERAD leads to accumulation of unfolded proteins in the ER, ER stress, and UPR induction, which were observed in HD models in yeast and mammalian cells (Duennwald and Lindquist, 2008; Reijonen et al, 2008; Carnemolla et al, 2009; Leitman et al, 2013, 2014), in animal HD models (Carnemolla et al, 2009; Cho et al, 2009; Noh et al, 2009; Vidal et al, 2012), and in post-mortem samples from HD patients (Carnemolla et al, 2009).…”
Section: Er Stress and Huntington's Diseasementioning
confidence: 99%
“…Although differences in phosphorylation between wtHtt and mHtt have been shown by various research groups, much less is known about differences in ubiquitination between wtHtt and mHtt. Several studies have reported the effects of ubiquitin ligases and deubiquitinating enzymes (DUBs) on aggregate formation by mHtt (15)(16)(17)(18)(19), indicating that altering the ubiquitination of mHtt improves the turnover of the mutant protein and decreases aggregate formation (20 -22). However, it is unknown whether mHtt is differentially ubiquitinated because of the polyQ expansion.…”
Section: Global Proteome and Ubiquitinome Changes In The Soluble And mentioning
confidence: 99%